Protective Effect of Vitamin C (Ascorbic Acid) Supplementation on Post-Thaw Motility and Fertility of Cryopreserved Rainbow Trout (Oncorhynchus mykiss) Sperm - Uğur Yavuz; Yusuf Bozkurt (Turkish Journal of Agriculture: Food Science and Technology)
Ascorbic acid (Vitamin C) is one of the important antioxidants, which naturally present in seminal plasma of fish. On the other hand, whether its effect may improve sperm quality following cryopreservation process still remains its uncertainty. Thus, the present study aimed to analyse the effect of different extenders supplemented with different ascorbic acid concentrations on post-thaw motility and fertility of frozen-thawed rainbow trout (Oncorhynchus mykiss) sperm. Selected sperm samples were pooled and diluted at 1:3 ratios with two different extenders (E) composing such as (E-1) 300 mM glucose, 10% egg yolk and 10% DMSO and (E-2) 0.6 mM sucrose and 10% DMSO. Each extender was supplemented with vitamin C at 1, 5 and 10 mM concentrations. Following dilution, the sperm was loaded into 0.25 ml straws and frozen in liquid nitrogen vapour. The straws were then plunged into liquid nitrogen for storage. Fertilization was carried out using the dry fertilization technique. Highest post-thaw motility (50±5.77) and fertilization (56±1.00) results were obtained with the extender-1 (E-1) containing 10% DMSO concentration. In conclusion, the present study indicated that addition of ascorbic acid to the extenders improved rainbow trout sperm motility resulting higher fertilization of the eggs.